Analisis Kualitas Pelayanan Maternal di Rumah Sakit: Pendekatan Literatur Naratif - Natalia, Dian; Ayuningytas, Dumilah (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2025)
Maternal mortality in Indonesia remains relatively high compared to other ASEAN countries, even though there has been a gradual decline over the past two decades. Various efforts have been made to improve the quality of maternal health services, particularly in hospitals that serve as primary referral centers. This study aims to examine the factors that influence the effectiveness of maternal care in hospitals and to explore intervention strategies that have contributed to reducing maternal mortality. A narrative literature review was conducted, analyzing 16 national and international journal articles published between 2020 and 2025. The findings show that service effectiveness is shaped by both clinical and non-clinical factors, including geographic access, socioeconomic disparities, human resource capacity, information system integration, and the strength of referral systems. In addition, context-sensitive health policies and multisectoral approaches play a critical role in supporting sustainable and impactful interventions for reducing maternal mortality.